Development of loop-mediated isothermal amplification assay for rapid diagnosis of pomegranate twig blight and crown rot disease caused by Coniella granati. (September 2020) - Yang, Xue; Gu, Chun-Yan; Abid, Muhammad; Al-Attala, Mohamed N.; Qin, Gai-Hua; Xu, Yi-Liu; May Phyo, Seinn Sandar; Zhang, Ai-Fang; Zang, Hao-Yu; Chen, Yu
Abstract: Twig blight and crown rot of pomegranate ( Punica granatum L.) is a destructive disease, caused by Coniella granati, a plant pathogenic fungus, leading to severe losses by damaging plant health, lowering fruit production, and deteriorating fruit quality. In this study, a sensitive loop-mediated isothermal amplification (LAMP) assay was developed for the rapid diagnosis of twig blight and crown rot disease of pomegranate caused by Coniella spp.. The assay is based on the use of four primers recognizing six distinct areas of translation elongation factor 1 alpha ( Tef-1α ) region (204 bp) of genomic DNA (gDNA) of Coniella spp. This LAMP assay detected Coniella spp . specifically among 23 fungal species isolated from different fruits including pomegranate in the Anhui Province of China. The assay was successfully evaluated for the minimum detection limit of 1 pg of crude DNA, which showed better sensitivity results using underoptimized LAMP reaction condition, at 65 °C for 60 min, which was superior to using conventional PCR. The resultant amplicons were easily detected by a visual examination in vials, using SYBR Green I, where they produced a yellowish green color for positive reactions, and were also identifiable by electrophoresis on the agarose gel. Thus, this LAMP assay can be used for the simple, fast, and precise diagnosis of twig blight and crown rot disease in suspected and infected parts of pomegranate plants. Highlights: Coniella spp. sensitive loop mediated isothermal amplification (LAMP) assay was developed. Rapid detection of twig blight and crown rot disease of pomegranate can be using the LAMP assay. The LAMP assay can be easily visual detected.